Penguatan Potensi Maritim melalui Peningkatan Usaha Pengolahan Hasil Perikanan dan Pendidikan di Desa Patuguran Kabupaten Pasuruan - Palupi, Hapsari Titi; Swasono, Muh. Aniar Hari; An Nabawy, Achmad Riefqy; Rizqi, Silfi Oktafiani; Rohima, Ainur Febrianti; Akhsani, Murikhatul; Isnaini, Nurul; Dayana, Putri; Dewitasari, Eka Aprilia; Zaidan , Muchammad (Kadiri University, 2025)
The objectives of the Community Service Program (KKN) in Patuguran Village are: 1) Building partnerships between students, the village government, and the community to create sustainable village development, especially in the maritime sector. 2) Increasing knowledge related to branding, packaging, and digital marketing of fishery product processing businesses as an effort to strengthen maritime economic potential. 3) Increasing knowledge and fostering a love of maritime potential through maritime creativity-based teaching activities for elementary school students. The methods used include observation, interviews, training, mentoring, creative teaching activities, and pre-test and post-test evaluations. Strengthening maritime potential through fishery product business development and maritime creativity education successfully achieved the expected goals. There was an increase in knowledge and interest among the village community to become entrepreneurs in fishery product processing. Training and mentoring in packaging, branding, and digital marketing led to the development of brands, labels, product packaging, and marketing channels through social media accounts, thereby enhancing product marketing. Educational activities with a maritime creativity theme for elementary school students increased students' knowledge about maritime potential, fostered a love of the maritime, and enhanced students' creativity and skills. These activities need to be continuously developed with a focus on economic empowerment and education as an effort to maintain the sustainability of maritime village development. Tujuan kegiatan KKN di Desa Patuguran adalah: 1) Membangun kemitraan antara mahasiswa, pemerintah desa dan masyarakat untuk menciptakan pembangunan desa yang berkelanjutan terutama dari sektor maritim, 2) Meningkatan pengetahuan terkait branding, pengemasan, dan digital marketing usaha pengolahan hasil perikanan sebagai upaya penguatan potensi ekonomi maritim, 3) Meningkatkan pengetahuan dan menumbuhkan kecintaan terhadap potensi maritim melalui kegiatan pengajaran berbasis kreativitas maritim bagi siswa sekolah dasar. Metode yang digunakan meliputi observasi, wawancara, pelatihan, pendampingan, serta kegiatan pengajaran kreatif, serta evaluasi pre-test dan post-test. Penguatan potensi maritim melalui pengembangan usaha hasil perikanan dan pendidikan kreativitas maritim berhasil mencapai tujuan yang yang diharapkan. Terdapat peningkatan pengetahuan dan ketertarikan masyarakat desa untuk menjadi pelaku usaha pengolahan hasil perikanan. Pelatihan dan pendampingan branding pengemasan, dan digital marketing menghasilkan merk, label, kemasan produk, serta saluran pemasaran melalui akun media sosial sehingga meningkatkan pemasaran produk. Kegiatan pendidikan dengan tema kreativitas maritim bagi murid sekolah dasar memberikan peningkatan pengetahuan siswa tentang potensi maritim, tumbuhnya rasa cinta maritim, serta meningkatkan kreativitas dan keterampilan siswa. Kegiatan ini perlu terus dikembangkan yang berfokus pada pemberdayaan ekonomi dan pendidikan sebagai upaya menjaga keberlanjutan pembangunan desa maritim.